Effect of Irrigation on Maize Yield (Zea mays L.) - Nagy, János (Acta Agraria Debreceniensis, 2003)
We have been continually examining the fertilizer and irrigation reaction of commonly cultivated maize hybrids for nearly twenty years at the Látókép experimental station of the Center for Agricultural Sciences, Debrecen University.Upon evaluating the results, it can be established that year significantly influences the size of yield. Between the years of 1999 and 2002, in the average of applied fertilizers the difference is 3,4 t/ha, but even in irrigated treatments it reaches 3 t/ha. This is more than the effect of irrigation. Of the applied agrotechnical elements, the yield increasing effect of fertilization is the greatest and can even be greater than the effect of year. The yield increasing effect of fertilization can be reliably detected with small and medium doses, but at higher doses a plateau section is reached, where it is not worth applying more nutrients. Cultivation with irrigation can only be done with appropriate nutrient supply, due to the positive correlation of the two factors. The positive correlation also means that if the water supply of the plant declines, less fertilizer is needed for safe production. The two factors (irrigation and fertilization) have to be increased or decreased at the same time.According to the experiment, in unirrigated treatments, 90 kg/ha nitrogen and the related phosphorus and potassium are enough, while in irrigated treatments this was 120 kg.